Family Support is the Key to Compliance with the Treatment of Relapsing Schizophrenia Patients - Betie Febriana; Wigyo Susanto; Dwi Heppy Rochmawati; Wahyu Endang Setiawati (Jurnal Ners, 2020)
Introduction: One problem in treating schizophrenia patients is relapse. The previous study results state that the biggest factor causing relapse is non-compliance with taking medication. This non-compliance with taking medication is influenced by several factors, including patient sociodemography, drug side effects, and family support. The purpose of this study was to determine the factors associated with medication adherence in Schizophrenia patients who were undergoing rehospitalization in an inpatient installation at RSJD in one city in Central Java, Indonesia.Methods: This study is a descriptive correlational analytic study with a cross-sectional approach. The population in this study were Schizophrenia patients who were undergoing re-hospital in the inpatient installation. Thirty-six samples were taken with the consecutive sampling method. The research instruments used were a socio-demographic questionnaire, family support questionnaire, Medication Adherence Rating Scale (MARS), and Glasgow Antipsychotic Side-effect Scale (GASS). Data analysis using descriptive analysis and chi-square test.Results: There is a relationship between family support for relapse in schizophrenia patients (p = 0.023).Conclusion: Researchers suggest that the hospital improves the treatment of family motivation to provide good support to patients to reduce the rate of re-hospitalization.